Residual stress characterization of shot peening using x-ray diffraction and eddy current testing - Mir Akbarkhan Mohammad Feroskhan (2018)
In shot peening, design engineers typically provide the desired peening intensity or desired residual stress value for the peening engineers to achieve. As there are no established relationships between peening intensity, residual stresses and the various material characteristics, they rely on empirical methods such as Almen Strip and experiences and guesses from past peening processes. This casts doubt on the validity of the shot peening process. Moreover, the inefficiencies of the current state of the art residual stress measurement methods motivates this study to combine the X-Ray Diffraction technique and the Eddy Current Testing method as a novel residual stress measurement method. This paper deals with nickel superalloys namely IN718 & IN625. The nickel specimens are shot peened at various intensities and subsequently, its conductivity measured by the Eddy Current Testing method. X-Ray Diffraction were also done to investigate the peening intensity vs residual stress relationship and to characterize the whole shot peening process. Eddy Current results indicated that the probe was not suitable due to its low frequency, hence going beyond the shot peening compressive residual stress layers. Thus, the Eddy Current method was unsuccessful. Subsequently, probe designs are suggested and the possibility of data conversion of electrical conductivity to residual stress demonstrated. X-Ray Diffraction results showed that the stress and cold work readings were not sufficient to ascertain the relationship mathematically and coupled with anomalous roughness data, it is not enough to tell if a shot peening process is done correctly. For now, only a crude relationship can be established for the peening intensity, residual stresses and the various material characteristics of the shot peening process.